2010
DOI: 10.1007/s10886-010-9830-2
|View full text |Cite
|
Sign up to set email alerts
|

Survey of a Salivary Effector in Caterpillars: Glucose Oxidase Variation and Correlation with Host Range

Abstract: Salivary glucose oxidase (GOX) has been reported in a few insect species where it plays a role in protection against infectious disease. Our recent research has focused on the role of this salivary enzyme in the noctuid Helicoverpa zea, where it functions as an effector to suppress the induced defenses of the host plant Nicotiana tabacum. In this study, we examined the labial gland GOX activities in 23 families of Lepidoptera (85 species) and two families of plant-feeding Hymenoptera (three species). We analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 59 publications
5
52
1
Order By: Relevance
“…The identification of glucose oxidase (GOX) as a component of Har salivary proteome (spot 3) was consistent with previous reports revealing the ubiquity of this enzyme not only within the family Noctuidae but across Lepidoptera [55], [56], [57]. GOX occurrence in Helicoverpa spp labial glands has been correlated with the inhibition of plant defences (e. g. nicotine production in tobacco) [11], [56] and bacterial protection [12].…”
Section: Resultssupporting
confidence: 89%
“…The identification of glucose oxidase (GOX) as a component of Har salivary proteome (spot 3) was consistent with previous reports revealing the ubiquity of this enzyme not only within the family Noctuidae but across Lepidoptera [55], [56], [57]. GOX occurrence in Helicoverpa spp labial glands has been correlated with the inhibition of plant defences (e. g. nicotine production in tobacco) [11], [56] and bacterial protection [12].…”
Section: Resultssupporting
confidence: 89%
“…20). Among the P. xylostella larval preferentially expressed genes, we identified a set of genes, including GOX (encoding glucose oxidase), related to the host range of herbivores 26 and involved in the perception of chemical signals from host plants and defense against secondary plant compounds (Fig. 4, Supplementary Table 25 and Supplementary Note), suggesting the presence of a complex chemoreception network and multiple detoxification mechanisms.…”
Section: (Supplementarymentioning
confidence: 99%
“…The Bede laboratory has been investigating the effect of saliva from larval S. exigua on modification of host proteins, and found that saliva is responsible for the cysteine oxidation of Rubisco and other proteins [46], which is not surprising considering the relatively high level of GOX in this insect [47]. Perhaps more intriguing were changes in the phosphorylation patterns of host proteins when dephosphorylation of a chaperonin at the Thr 59 and lipoxygenase 2 at Ser 600 occurred [46].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the synthesis and secretion of salivary proteins such as GOX is host-specific [58][59][60][61], while also varying among different caterpillar species [47]. Within the same species, the amount of dietary protein or glucose is correlated with the salivary GOX activity [47,62,63]. Thus the composition of both oral secretions and saliva from insect herbivores is highly dependent upon their host plant and the herbivore.…”
Section: Introductionmentioning
confidence: 99%